PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN BAKSO GRANAT MAS AZIZ (CABANG BUKIT PALEMBANG) - Muhammad Deni (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2022)
This research was conducted with the aim of knowing the effect of price and product quality on consumer decisions of Mas Azis grenade meatballs Palembang branch. This study uses associative descriptive analysis, namely research that seeks to find the influence or relationship between one or more. The sample used in this study were 96 consumers of Mas Azis grenade meatballs Palembang hill branch. The data collection techniques and research information used in this study were interviews and questionnaires. The approach method used is a quantitative approach. The data analysis method in this study uses multiple linear regression analysis and hypothesis testing using the T test and F test. In this case, the researcher manages to use data calculations through the SPSS 25 program. Based on the results of the study, it is known that there is a positive and significant influence between price on purchasing decisions of Mas Azis grenade meatballs, Palembang hill branch. It is known that the value of sig t of the price variable (X1) is 0.002 < = 0.05 and tcount > ttable (3.175 > 1.661). There is a positive and significant influence between product quality on purchasing decisions of Mas Azis grenade meatballs Palembang hill branch. It is known that the sig t value of the product quality variable (X2) is 0.000 < = 0.05 and tcount > ttable (3.777 > 1.661). There is a positive and significant influence between price and product quality on the purchase decision of Mas Azis grenade meatballs Palembang branch. It is known that the value of sig F is 0.000 < 0.1 and Fcount > Ftable (43.977 > 2.36). The value of R Square is 0.486 which indicates that the relationship between price and product quality variables affects purchasing decisions by 48.6%.